2016
DOI: 10.1002/adma.201603528
|View full text |Cite
|
Sign up to set email alerts
|

Graphite‐to‐Graphene: Total Conversion

Abstract: The rush to develop graphene applications mandates mass production of graphene sheets. However, the currently available complex and expensive production technologies are limiting the graphene commercialization. The addition of a protective diluent to graphite during ball-milling is demonstrated to result in a game-changer yield (>90%) of defect-free graphene, whose size is controlled by the milling energy and the diluent type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 28 publications
10
124
0
Order By: Relevance
“…To protect the structural integrity of 2D crystals, buffers are added to reduce the momentum of the grinding body during ball milling . For instance, Buzaglo et al have shown that aromatic reagents with higher conjugation degree leads to graphene sheets with high quality . In addition, by adding active ingredients appropriate media during ball milling, functional 2D crystals can be achieved.…”
Section: Preparation Of 2d Crystal–based Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…To protect the structural integrity of 2D crystals, buffers are added to reduce the momentum of the grinding body during ball milling . For instance, Buzaglo et al have shown that aromatic reagents with higher conjugation degree leads to graphene sheets with high quality . In addition, by adding active ingredients appropriate media during ball milling, functional 2D crystals can be achieved.…”
Section: Preparation Of 2d Crystal–based Fibersmentioning
confidence: 99%
“…[27,171] For instance, Buzaglo et al have shown that aromatic reagents with higher conjugation degree leads to graphene sheets with high quality. [172] In addition, by adding active ingredients appropriate media during ball milling, functional 2D crystals can be achieved. For example, Jeon and co-workers used 2M NaOH as additives during milling and ultrasonicating h-BN, and obtained dispersions of 2D h-BN with hydroxyl groups.…”
Section: Mass Production Of 2d Crystals and Their Dispersions By Exfomentioning
confidence: 99%
“…The approach to produce graphene via ball milling has been widely investigated. [28][29][30][31][32][33][34][35] Baek's group found that edge-functionalized graphene nanoplatelets could be prepared by dry ball milling in the presence of hydrogen, carbon dioxide, or sulfur trioxide which acts as an electrocatalyst for the oxygen reduction reaction. 28,29 Salt such as sodium chloride or sodium sulfate is added to facilitate the delamination of graphite.…”
Section: Mechanochemical Reaction Of Graphitementioning
confidence: 99%
“…36,37 To avoid this problem, a protective agent such as naphthalene, pyrene, melamine, or ammonia gas is introduced during ball milling. [32][33][34][35] Although these additives help produce high-quality FLG, the thickness is usually not uniform and the milled powder can only be dispersed in NMP, DMF, or a water/surfactant solution.…”
Section: Mechanochemical Reaction Of Graphitementioning
confidence: 99%
“…Thus, the carbon family consists of each dimensional material: fullerene in zero dimensions [5]; carbon nanotube in one dimension [6]; graphene in two dimensions (2D); and graphite in three dimensions (3D). Graphene, a one-atom thick layer of sp 2 hybridized carbon atoms arranged into hexagonal crystal, has been a topic of interest in nano-science due to its excellent properties and the prospect of industrial applications [7][8][9][10]. Owning to its unique structure, the charge carrier mobility of graphene exceeds 2.0 × 10 5 cm 2 ·V −1 ·s −1 at room temperature which is 100 times higher than that of silicon [11].…”
Section: Introductionmentioning
confidence: 99%